Bio-inspired flexible structures improve energy capture and reduce wave loads in oscillating water columns - Korkmaz, Fatih C.; Gedikli, Ersegun D. (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Wave energy is a highly promising renewable resource, but traditional Oscillating Water Columns (OWCs) often struggle to efficiently capture energy across a broad range of wave frequencies. This study investigates the integration of artificial stems, inspired by natural kelp structures, to enhance the resonance properties and energy absorption capabilities of OWCs. A novel experimental approach is employed to analyze the dynamic response of OWCs with varying stem configurations under diverse wave conditions. Key performance indicators-including energy capture efficiency, frequency response, and structural integrity-are discussed. Results show that artificial stems significantly improve energy extraction by broadening the effective frequency range and mitigating wave-induced structural stresses, with strain measurements revealing up to a 70% reduction in peak stresses on the OWC's front plate. The presence of stems also increases the rising time of wave impacts by as much as 60%, shifting loads from impulsive to quasi-static regimes and thereby enhancing structural safety. Additionally, the influence of stem material properties and geometric arrangements is examined, highlighting an optimal stem configuration that reduces impulsive loading without diminishing airflow needed for turbine operation.
Keywords: Wave energy; Oscillating water columns; Artificial stems; Efficiency; OWC; CYLINDER; Engineering; Oceanography